2011
DOI: 10.1051/epjap/2011100305
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the current density distribution in electrochemical cells based on the level set method and genetic algorithm

Abstract: Abstract. This paper proposes a general applicable algorithm for the optimization of the current density distribution in the electrochemical cells using the insulating shields during the electroplating process. The innovative aspect is that the position of the insulating shield is displaced over a number of predefined time steps convecting its surface proportional with and in the direction of a well chosen rate provided by a genetic algorithm. The aim of this method is to develop a systematic modification of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…During the last two decades, significant work on developing methods for modelling electrochemical cells has been done in the University of Brussels 10-13 and these methods have been applied to simulating various industrial processes. [14][15][16][17][18] Practical simulation studies of laboratory and industrial scale plating processes have also been made by other research groups [19][20][21][22][23] and some studies of developing the layout of the plating tank 16,[24][25][26] can be found. However, to the authors' knowledge, the elementary configuration of the plating tank has not been developed as extensively as in this study.…”
Section: Introductionmentioning
confidence: 99%
“…During the last two decades, significant work on developing methods for modelling electrochemical cells has been done in the University of Brussels 10-13 and these methods have been applied to simulating various industrial processes. [14][15][16][17][18] Practical simulation studies of laboratory and industrial scale plating processes have also been made by other research groups [19][20][21][22][23] and some studies of developing the layout of the plating tank 16,[24][25][26] can be found. However, to the authors' knowledge, the elementary configuration of the plating tank has not been developed as extensively as in this study.…”
Section: Introductionmentioning
confidence: 99%